Utility Of An Automatic Limulus Amebocyte Lysate Kinetic Turbidimetric Test For Endotoxin Screening Of Dialysate Samples - Uchida T (Dove Medical Press, 2019)
Takayuki Uchida,1,* Yoshio Kaku,2,* Hideyuki Hayasaka,1 Masaya Kofuji,1 Naoki Momose,1 Haruhisa Miyazawa,2 Yuichiro Ueda,2 Kiyonori Ito,2 Susumu Ookawara,2 Yoshiyuki Morishita2 1Department of Clinical Engineering, Saitama Medical Center, Jichi Medical University, Saitama-City, Saitama, Japan; 2Division of Nephrology, First Department of Integrated Medicine, Saitama Medical Center, Jichi Medical University, Saitama-City, Saitama, Japan*These authors contributed equally to this workCorrespondence: Yoshiyuki MorishitaDivision of Nephrology, First Department of Integrated Medicine, Saitama Medical Center, Jichi Medical University, 1-847 Amanuma-cho, Omiya-ku, Saitama-City, Saitama 330-8503, JapanTel +81-48-647-2111Fax +81-48-647-6831Email ymori@jichi.ac.jpBackground: Endotoxin contamination of dialysate has serious adverse effects on patients undergoing hemodialysis. Therefore, endotoxin activity in dialysate is closely monitored. Limulus amebocyte lysate (LAL) has been used as a reagent to measure endotoxin activity. Here, we investigated the efficacy of an automatic LAL kinetic turbidimetric test (Toxinometer ET-mini) for screening endotoxin activity in dialysate.Methods: In total, endotoxin activity was measured in 110 dialysate samples obtained from several sites within hemodialysis circuits between June 2012 and March 2018. The results were compared with those from a conventional chromogenic substrate LAL test conducted by a clinical examination laboratory.Results: Both the automatic LAL test and the chromogenic substrate LAL test had a minimum detection level of 0.001 endotoxin units (EU)/mL. Endotoxin activity levels measured via the automatic LAL test showed a strongly positive correlation (concordance correlation coefficient: 0.9933; 95% CI: 0.9902–0.9954) and good agreement (mean difference: 0.00±0.01 EU/mL) with those obtained using the chromogenic substrate LAL test.Conclusion: The results suggest that the automatic LAL test may be useful for endotoxin activity screening in hemodialysis facilities.Keywords: endotoxin, dialysate, hemodialysis, limulus amebocyte lysate, chromogenic substrate